Monetary Transmission in the Euro Area : Where Do We Stand? - Benoît Mojon; Anil K. Kashyap; Ignazio Angeloni; Daniele Terlizzese (European Central Bank (ECB), 2002)
Drawing on recent Eurosystem research that uses a range of econometric techniques and a number of new data sets, we propose a comprehensive description of how monetary policy affects the euro area economy. We focus mainly on three questions: (1) what are the stylised facts concerning the transmission of monetary policy for the area as a whole and for individual countries? (2) can the 'classic' interest rate channel (IRC) alone, without capital market imperfections, explain these facts? (3) if not, is the bank lending channel a likely candidate to complete the story? We find plausible euro-area wide monetary policy responses for prices and output that are similar to those generally reported for the US. However, investment (relative to consumption) seems to play a larger role in euro area monetary policy transmission than in the US. We cannot reject the hypothesis that the IRC completely characterises transmission in a few countries, and estimate it to be substantial in almost all. Where the IRC is not dominant, there is normally some direct evidence supporting the presence of a bank lending channel (or other financial transmission channel). The cases where financial effects appear important can be further split according to whether they primarily relate to consumption or investment
Keywords: E52; E58; E44; 330; bank lending; euro area; monetary policy; transmission mechanism